Optimization and analysis of rib working resistance in push-the-bit rotary steerable drilling system. - Jianbo Jia; Youhong Sun; Ke Gao; Yan Zhao; Bing Li; Xu Li (PLoS ONE)
The rib working resistance of push-the-bit rotary steerable drilling system seriously affects its dynamic performance. For example, the backing pressure problem caused by steps in the well wall during the working process of CNOOC Welleader static push-the-bit rotary steerable drilling tool is discussed in this paper. Based on the structure and working principle of CNOOC Welleader system, a corresponding theoretical model of force analysis is established, and an optimal design method to reduce the backing pressure problem is proposed in combination with numerical simulation and experimental research. The results show that changing the front chamfer area of Welleader system from circular arc to polyline is beneficial to reducing the backing pressure problem. The simulation results show that for steps of 1mm, 2mm and 3mm height, the optimal polyline angle is concentrated in the range of 10°-11°, in which the Angle of 10.5° has a good performance against the steps of three heights. Finally, by making corresponding test blocks, it was found that the peak value of forward resistance when the 10.5°test block crossed the steps of 1mm, 2mm and 3mm height decreased by 19.8%, 25.0% and 13.9% respectively, and the mean value decreased by 30.8%, 27.2% and 24.1% respectively, which was close to the simulation results, and verified the accuracy of the finite element analysis results.